Direct estimation of the area under the receiver operating characteristic curve with verification biased data - Hai, Yan; Qin, Gengsheng (Statistics in medicine, 2020)
In medical diagnostic studies, verification of the true disease status might be partially missing based on results of diagnostic tests and other characteristics of subjects. Because estimates of area under the ROC curve (AUC) based on partially validated subjects are usually biased, it is usually necessary to estimate AUC from a bias‐corrected ROC curve. In this article, various direct estimation methods of the AUC based on hybrid imputation [full imputations and mean score imputation (MSI)], inverse probability weighting, and the semiparametric efficient (SPE) approach are proposed and compared in the presence of verification bias when the test result is continuous under the assumption that the true disease status, if missing, is missing at random. Simulation results show that the proposed estimators are accurate for the biased sampling if the disease and verification models are correctly specified. The SPE and MSI based estimators perform well even under the misspecified disease/verification models. Numerical studies are performed to compare the finite sample performance of the proposed approaches with existing methods. A real dataset of neonatal hearing screening study is analyzed.